Вы находитесь на странице: 1из 31

-

( )

..

, 2004

..
517.

.
- ( 2- ).
. ., 2004. 31 .


,
, .

. ,
.

.

c - , 2004

c .., 2004

1.
. . . . . . . . . . . . . . . . . . . . .
2. . . . . . . . . . . . . .
3. . . . . .
4.
. . . . . . . . . . . . . . . . . . . .
5.
.

. . . . . . . . . . . . . . . . . . . . .
. . . . . . . . . . .

4
10
13
18

22
30



1.

1.1.

a0 X
+
ak cos kx + bk sin kx (ak , bk R)
2
k=1

.

1
, cos x, sin x, cos2x, sin 2x, cos 3x, sin 3x, . . .
2
.
,
Z
cos kx cos mx dx = 0, k, m N0 , k 6= m,

Z
sin kx sin mx dx = 0, k, m N0 , k 6= m,
Z

cos kx sin mx dx = 0, k, m N0 , m N.

,
Z
Z
2
cos kx dx =

sin2 kx dx = ,

k N.

1.1.

f (x) =

a0 X
+
ak cos kx + bk sin kx,
2
k=1

(1.1)

1. .

R.
Z
1
a0 =
f (x) dx,

Z
1
ak =
f (x) cos kx dx,

Z
1
bk =
f (x) sin kx dx, k N.

(1.2)

. f
[, ]
. (1.1) cos nx
sin nx (n N).
Z
Z
f (x) cos nx dx =
an cos2 nx dx = an ,

Z
Z
f (x) sin nx dx =
bn sin2 nx dx = bn ,

(1.2). (1.2)
(1.1).
,
2-
. (
) 2- .
1.2. f 2- , [, ]. ak , bk , (1.2), ()
f , ak , bk
f .

. . .

a0 X
f (x)
+
ak cos kx + bk sin kx,
2

(1.3)

k=1

, f .
1.1 :
.
1.1. ,

P
sin kx , > 0, .
1+
k=1

, 2- f
- [a, a+2] 2,

[b, b + 2]
Z b+2
Z a+2
f (x) dx =
f (x) dx.
b

, ,
. , 2- f ,
(1.2) [, ] [a, a + 2].
, [a , a + ] ( a a + ,
)
2- .
2 (1.2), , (1.3).
, , f
2, , [, ].

1. .


, ,
..
, f
f . , f
.
1.1 ( ).
f (a, b).
Z b
Z b
lim
f (x) cos x dx = lim
f (x) sin x dx = 0.
a

. , (a, b) = (, +) ( , f
(, +) \ (a, b)). ,
(, ) f , ..
Z +
|f (x + h) f (x)| dx 0 h 0.
(1.4)

, f
.
x x +
, :
Z +
Z + 

I() B
f (x) cos x dx =
f x+
cos x dx =

Z
i
1 + h 

=
f x+
f (x) cos x dx.
2

(1.4)
Z

1 + 


|I()| 6
f
x
+

f
(x)

dx 0 ( ).
2

R +
f (x) sin x dx .

. . .

1. (1.2) [, ]
k .
2- f [, ].
n

a0 X
Sn (x; f ) B
+
ak cos kx + bk sin kx
2
k=1

n N0 f . , .



1 x
n
sin
n
+
X
1
2
Dn (x) B +
cos kx =
.
(1.5)
x
2
2 sin 2
k=1

( x =
= 2m, m Z, x 2m) . x 6= 2m
!
n
1
x X
x
Dn (x) =
sin +
2 sin cos kx =
2 sin x2
2
2
k=1
!
n
1
x X
2k + 1
2k 1
=
sin +
sin
x sin
x =
2 sin x2
2
2
2
k=1


sin n + 12 x
=
.
2 sin x2
(1.5) , , 2-,
, ,
1
max |Dn (x)| = Dn (0) = n + ,
2
Z
Z
1
2
Dn (x) dx =
Dn (x) dx = 1.
(1.6)
0

1. .

Sn (x; f ),
(1.2).
Sn (x; f ) =
Z
Z
n
X
1
1
f (t) dt +
f (t)(cos kt cos kx + sin kt sin kx) dt =
=
2

k=1
"
#
Z
n
1 X
1
f (t)
+
cos k(t x) dt
=

2
k=1
Z
1
Dn (t x)f (t) dt. (1.7)
=

(
) t t + x ,
Z
1
Sn (x; f ) =
Dn (t)f (x + t) dt =

Z 0 Z 
1
=
+
D(t)f (x + t) dt =

0
Z
1
=
Dn (t)[f (x + t) + f (x t)] dt. (1.8)
0
, 0 < < ,

 
Z Z 
1
1
f (x + t) + f (x t)
Sn (x; f ) =
sin
n+
t dt.
+
2

2 sin 2t
0

2 sin 2t >
> 2 sin 2 > 0,
t.
, n
. ,
, .

10

. . .

1.2 ( ). 2- f [, ],
x0 R, 0 < < .
lim Sn (x; f ),

1
lim
n

f (x0 + t) + f (x0 t)



1
n+
2

 
t dt

sin
2 sin 2t

.
, ,
f x0 f (x0
, x0 + ), .. x0 .
0

2.
x0 f .
:
f (x0 + h) f (x0 + 0)
f+0 (x0 ) = lim
,
h0+0
h
f (x0 h) f (x0 0)
,
f0 (x0 ) = lim
h0+0
h
.
2.1. x0
f , f (x0 + 0), f (x0 0), f+0
f (x 0) + f (x + 0)

0
0
, x0
+(x0 ), f0 (x0 ). f (x0 ) =
2
f .
f x0
, x0 f .

2.1. 2- f [, ], x0 . f
x0

f (x0 0) + f (x0 + 0)
. x0
2

2. .

11

f ( , f x0 ),
x0 f (x0 ).
. x0
f . (1.8) (1.6)
f (x0 0) + f (x0 + 0)
=
Z 2
1
=
Dn (t)[f (x0 + t) + f (x0 t)] dt
0
Z
f (x0 + 0) + f (x0 0) 2

Dn (t) dt =
2
0

 
Z
1
f (x0 + t) + f (x0 t) 2f (x0 )
1
=
sin
n+
t dt =
0
2
2 sin 2t
Z 
1 f (x0 + t) f (x0 + 0)
=
+
0
t
 
 

1
f (x0 t) f (x0 0)
t
sin n +
t dt.
+
2
t
2 sin 2t

Sn (x; f )

t , t = 0, 2 sin 2t
f (x0 + t) f (x0 + 0)
[0, ] .
t

[0, ] , , t 0+0
. 


1
. , sin n + 2 t
[0, ] .
,
n , ..
f (x0 0) f (x0 + 0)
Sn (x0 ; f )
n .
2
2.1. f+0
+(x0 ), f0 (x0 ) ( -

12

. . .

|f (x0 + h) f (x0 + 0)| 6 M h ,

|f (x0 h) f (x0 0)| 6 M h ,

h (0, ),
h (0, ),

(2.1)

(0, 1], > 0, M > 0. (2.1) () ,


= 1 () .
1. 2- f [, ], f 0 (x0 ).
f x0 f (x0 ).
2.2. R 2-
x0 . 2- R ,
.
2.1, 2.1 .
.
2.3. f
2,
[, ]. 2.1, f ( ) 2- .
x = ,
f+0 (), f0 (). f
f ( + 0) + f ( 0)

x0 =
.
2

x0 = .
x
2.1. f (x) =
2 ,x
[0, 2].

3. .

13

f: R R 2- , f(x) = f (x)
0 < x < 2, f(0) = 0. ,
f (1.2) . f, ak = 0 k N0 . ,
Z
1 2 x
bk =
sin kx dx =
0
2

Z 2
1
cos kx 2
1
1
= ( x)

cos kx dx = .

x 0
2k 0
k
, x R f. ,
f(x) =

X
sin kx
k=1

x R.

(2.2)

, [0, 2] f f f (0, 2) f
.

3.
3.1. f - [a, b], {ai }m
i=0 [a, b] (a = a0 < a1 < a2 < <
< bm = b), :
1. f 0
(ai1 , ai );
2. f 0 (ai1 + 0), f 0 (ai
0) i = 1, 2, . . . , m.
2- - (- ), - (- )
[, ].

14

. . .

3.1. f 2-
- .
f f R

ln n
sup |Sn (x; f ) f (x)| 6 C
n > 2,
n
xR
C n.
. M0 = max |f |, M1 = max |f 0 |,
f (x + t) + f (x t) 2f (x)
gx (t) B
.
2 sin 2t
, 0 < t 6
|f (x + t) + f (x t) 2f (x)| 6 2M1 t.
,
|gx (t)| 6

2M1 t
2 sin 2t

6 M1 ,



d

gx (t) 6 |f 0 (x + t) f 0 (x t)| 1 +

dt
2 sin t
2

+|f (x + t) + f (x t) 2f (x)|

cos 2t

6
4 sin2 2t

M1 2 M1
2 M1
+
6
.
t
2t
t
0 < = n < . 2.1
Z Z 

 
1
1
Sn (x; f )f (x) =
+
gx (t) sin
n+
t dt = In +Jn .

2
0

, |In | 6 M1 .
C




1 t
1 t
Z
cos
n
+
cos
n
+
1
1
d
2
2
Jn = gx (t)

gx (t)
dt.

1
1

dt
n+ 2
n+ 2

3. .

15

|Jn | 6

M1


nM

1
 1  = 1+
+
M1
.
1

n+ 2
n + 12
n + 12

1 , , n > 2
= n = n

sup |Sn (x; f ) f (x)| 6 |In | + |Jn | 6


xR

C ln n
,
n

C n.
.
, 3.1 ,
.
,
3.1, , , .
. , f : [a, b] R , 0 < 6 1 (
= 1), M > 0:
|f (x) f (y)| 6 M |x y|

x, y [a, b].

, , , , .
f - [a, b], [a, b] .
3.1.
3.2. 2- f R , 0 < 6 1.
R
ln n
sup |Sn (x; f ) f (x)| 6 C
n > 2,
n
x

16

. . .

C n.
. (2.1)


 
Z
1 f (x + t) f (x)
1
sin
n+
t dt.
Sn (x; f ) f (x) =

2
2 sin t
2

hx (t) =

f (x + t) f (x)
2 sin 2t

= n = n +

1
,
2

>

>2 .
n

, ,
Z

1 


|Sn (x; f ) f (x)| 6
hx (t) dt =
hx t +
2

Z Z 
Z
1
1
=
. . . dt +
+
. . . dt = I,n (x) + J,n (x). (3.1)
2
2

, 2 t < sin t < t 0 < t < 2 . ,


|t| 6 2
M |t|

|hx (t)| 6
= M |t|1 ,
2|t|
2

Z 2

I,n (x) 6 M
t1 dt =
M 2 .
(3.2)
2
2
0
|t| > ,


hx t +

hx (t) =



f x+t+
f (x)
t+
2 sin 2

f x+t+
f (x)
t+
2 sin 2

f (x + t) f (x)
2 sin 2t

t
t+
sin
2
sin 2
(f (x + t) f (x)),

(3.3)

3. .

17

 

2 M |t|



2 sin 2
M




+


hx (t) 6
6
hx t +




|t|

2 t +
2
t
+

6 C2
Z
J,n (x) 6

M
,
|t|

C2 M dt
C2 M 1
6
ln .

8 , = n

.
3.1,
, .
3.3. 2- f [, ].
(a0 , b0 ) f f 0 -.
f f
[a, b] (a0 , b0 ).
8 6 < , [a 2, b + 2]
. n
(a0 , b0 ), x [a, b]. (3.1). (3.2)
= 1
I,n (x) 6 C1 M1 .
J,n (3.3)
.
Z 

1



J,n (x) 6
f (u) du+
f u +
4

!
Z
3
+ 2
|f (u)| du + 2 sup |f | .
4

[a,b]

> 0.
= () > 0, sup I,n < 2 .
[a,b]

n N : sup J,n <


[a,b]

n > n .

18

. . .

(3.1) ,
sup |Sn (x; f ) f (x)| 0 n
x[a,b]

.
, 3.3 , ,
[a, b]
(a , b + )
> 0.

P
sin kx 3.3 , ,
k
k=1

[, 2 ], > 0,
x
f (x) =
2 .
3.3 ,
> 0 [a0 , b0 ].

4.

4.1.
n
A0 X
+
Ak cos kx + Bk sin kx (A2n + Bn2 > 0)
2
k=1

( ) n.
4.1 (). f 2- . > 0
T ,
max |f (x) T (x)| < .
xR

. > 0. = {xj }Jj=0 ,


xj = + j 2
J , [, ]. ( f ),

4. .

19

(xj , f (xj )) f .
J : R R 2- ,
[, ] . ,
J [, ] , , (.. 0J -).
f .

|f (x0 ) f (x00 )| <

|x0 x00 | 6

2
,
J

J = J() N .

max |f (x) J (x)| < .


2
J 2.1,
R. ,
n = n(),

max |j (x) Sn (x; J )| < .


xR
2
,
max |f (x) Sn (x; J )| < ,
xR

..
T (x) = Sn (x; J ).
4.1
:
4.10 . (). f [, ] f () = f ().
> 0 T ,
max |f (x) T (x)| < .

6x6

20

. . .

4.1. , , f () = f ().
, 4.1
T ( ) Sn (x; f ) (
f ), (
) f . , T
n (x; f ) ( f ) n,
S0 (x; f ) + S1 (x; f ) + + Sn (x; f )
n (x; f ) =
n+1
, :
4.2 (). f 2- .
n (x; f ) f (x) n .
R

.
:
2- f f (x) .
( )

.

.
4.1. 11+11+. . .
12 .
4.1 () P .

4. .

21

4.3 (). f [a, b]. > 0


P ,
max |f (x) P (x)| < .

a6x6b

. [0, ]
[a, b]:
ba
x=a+
t, 0 6 t 6 , a 6 x 6 b,



a t , 0 6 t 6 . f (t) = f a + b

[, 0]
2, f . f : R R
2- R. 4.1
> 0 T ,

max |f (t) T (t)| 6 max |f (t) T (t)| < .


06t6
xR
2
cos kt, sin kt ( T (t)) R = +, , ,
. n = n(),

max |T (t) Pn (t)| < ,


06t6
2
Pn T .
,

max |f (t) Pn (t)| < + = ,
06t6
2 2
( x)




x a

max f (x) Pn
< .
a6x6b
ba
.
4.3 :

22

. . .

[a, b]
.

5.
.

5.1. 2- f -

a0 X
+
ak cos kx + bk sin kx
f (x) =
2
k=1

X
f 0 (x)
kak sin kx + kbk cos kx,
k=1

..
.
.

0 X
f 0 (x)
+
k cos kx + k sin kx.
2
k=1

, ,
Z
1 0
1
0 =
f (x) dx = [f () f ()] = 0,

Z
1
k =
f 0 (x) cos kx dx =


Z

1
k
= f (x) cos kx +
f (x) sin kx dx = kbk ,

Z
1 0
k =
f (x) sin kx dx =


Z

k
1

= f (x) sin kx
f (x) cos kx dx = kak .

5. .

23

5.1. 2- f m 1 - m N.
f



1
|ak | + |bk | = o
k .
(5.1)
km
. m > 1

X
f (m) (x)
k cos kx + k sin kx.
k=1

m 5.1, ,
|k | + |k | = k m (|ak | + |bk |),

k N0 .

k , k 0 (k )
, (5.1).
5.1 , f
,
f .
5.1 , - 2 :
Z

1 2
a0 X 2
+
(ak + b2k ) 6
f (x) dx.
(5.2)
2

k=1

. (5.2)
f (m) , , 5.1
Z

X
1 (m)
2m 2
2
k (ak + bk ) 6
(f (x))2 dx < .

k=1

. , -

24

. . .

2- f , ..

X
f) B
S(x;
ak sin kx bk cos kx,
(5.3)
k=1

ak , bk f .



x cos n + 1 x
n
cos
X
2
2
n (x) =
D
sin kx =
.
x
2 sin 2
k=1

, (1.5).
, (1.8) ,
n
X

S n (x; f ) =
ak sin kx bk cos kx
k=1

(5.3)
Z
n (t)[f (x + t) f (x t)] dt =
Sn (x; f ) =
D
0

1
=


hx (t) cos

1
n+
2

f (x + t) f (x t)

hx (t) B
1
f(x) B

2 sin 2t

Z
0

f (x + t) f (x t)
2 tg 2t

 
t dt + f(x),

dt.

5.2. 2- f
- , ak , bk .
C > 0 n > 2


X

ln n


sup
ak sin kx bk cos kx 6 C
.
(5.4)

n
xR
n+1

5. .

25

. M1 B max |f 0 |. R


|f (x + t) f (x t)| 6 2M1 t,

0 < t 6 ,

, , f(x)
x ( (0, ] ).


Z
1
1

hx (t) cos n +
t dt,
f (x) S n (x; f ) =
0
2

|hx (t)| 6 M1 ,



d
hx (t) 6 |f 0 (x + t) + f 0 (x t)| 1 +

dt
2 sin t
2

+|f (x + h) f (x h)|

cos 2t

6
4 sin2 2t

M1 2 M1
2 M1
+
6
.
t
2t
t

, 1.2
ln n
sup |f(x) Sn (x; f )| 6 C
n
xRn

n > 2,

(5.4).
5.2. m N 2-
f m 1 - f (m) .
f f


ln n
max |f (x) Sn (x; f )| = O
=
xR
nm


1
=o
n > 0.
nm

26

. . .

. m = 1 3.1. B f (m1) k , k
. 3.1


X

ln n


sup
n > 2.
(5.5)
k cos kx + k sin kx 6 C

n
xR
k=n+1

ak , bk f .
m1 . m1 5.1
x R


X



|rn (x; f )| =
ak cos kx + bk sin kx =


k=n+1


X
1


=
(
cos
kx
+

sin
kx)
.
k
k


k m1
k=n+1

,
P

k cos kx + k sin kx (k=n+1

m = 1 )

X

ln n


sup
k cos kx + k sin kx 6 C
.

n
xR
k=n+1

X
X

|rn (x; f )| =
j cos jx + j sin jx

j=n+1
k=n+1





X

1
1
ln
n
1
1


6
C



=
(k + 1)m1 k m1
n
(k + 1)m1 k m1
k=n+1

=C
(5.5) .

ln n
1
ln n
6C m ,
m1
n (n + 1)
n

5. .

27

m 1 .


X


|rn (x; f )| =
ak cos kx + bk sin kx =


k=n+1


X
1


=
(
sin
kx

cos
kx)
.
k
k


k m1
k=n+1

k sin kx k cos kx 5.2. -

k=n+1

(5.5), ,

X
X

|rn (x; f )| =
j sin jx j cos jx

k=n+1 j=n+1


1
1
ln n
1
ln n

m1 6 C
6C m ,
m1
m1

(k + 1)
k
n (n + 1)
n
.
5.2 ,
f , .
. 5.1 5.2 f , [, ],
,
2-
5.1 5.2. , f :
[, ] R :
f (j) () = f (j) () j = 0, 1, . . . , m 1.
3.1 5.1 f : [, ] R f () = f ().
5.2 5.20 ,
, -

28

. . .

2- .
5.20 5.2
, (5.2), .
.
5.3. f 2- - , ak , bk .
(5.2).
. f 2- - . 5.2, :

f (x) =

a0 X
+
ak cos kx + bk sin kx.
2

(5.6)

k=1

(5.6) f (x)
( ) . (1.2)
Z

a0 X 2
1 2
2
+
(ak + bk ) =
f (x) dx,
(5.7)
2

k=1

(2.2)
(5.7) (5.2) f
.
f
J : R R 2- ,
[, ],
4.1 ( J

5. .

29

f ). ak (f ), bk (f ) f . (5.2)
n
a20 (J ) X 2
+
(ak (J ) + b2k (J )) 6
2
k=1
Z
1 2
(x) dx n N. (5.8)
6
J
n N , J . , ,
Z
Z
2
ak (J ) ak (f ), bk (J ) bk (f ),
J (x) dx f 2 (x) dx.

(5.5), ,
Z
n
1 2
a0 (f ) X 2
2
+
(ak (f ) + bk (f )) 6
f (x) dx.
2

k=1

n ,
.
5.20 . m N 2-
f m 1 - f (m) .
f
R


1
max |f (x) Sn (x; f )| = o
n .
(5.9)
1
xR
nm 2
.
f 3.1.
.


X



|rn (x; f )| =
ak cos kx + bk sin kx 6


k=n+1

X
k=n+1

(|ak | + |bk |) 6

X
k=n+1

(|k | + |k |)

1
,
km

30

. . .

k , k f (m) ,
m- 5.1.

v
v
u N
u N
N
X
u X
u X 1
1
t
2
(|k | + |k |) m 6
(|k | + |k |) t
.
k
k 2m
k=n+1

k=n+1

k=n+1

N
, , N . , ,
v
v
u X
u X

u
u
1
2
2
t
|rn (x; f )| 6 2
(k + k )t
=
2m
k
k=n+1
k=n+1
v
u X
u
1
= n t
, (5.10)
2m
k
k=n+1

n 0 (n )

P
k=1

(k2 +

+ k2 ), f (m)
(. 5.3). ,
Z

Z m
X
X
1
dx
dx
1
6
6
=
.
2m
2m
2m
k
(2m 1)n2m1
k1 x
n x
k=n+1

k=n+1

(5.10) (5.9).


, 2l- . .

, -

31